Assessment of Salivary Flow Rate and Carbon Monoxide Level among Smokers, Tobacco Chewers and Control Group - Manju J; Krithika C; Karthikeyan G; Karishma Chowdary M.V; Karthika R; Mugesh Raj S (Indian Journal of Forensic Medicine & Toxicology, 2021)
Aim: To assess salivary flow rate and carbon monoxide level among smokers, tobacco chewers and controlgroup.Methodology: The study has total of 45 subjects, which were divided into 3 groups and 15 subjects in each.Group A- smokers’ group, Group B- chewers’ group, Group C-control group. Unstimulated whole salivawas measured by performing modified Schirmer tear strip test(MST). Smokerlyzer used for measuring COlevels from exhaled breath.Result: On analysing the data of SFR between smokers, chewer’s and control group, there was statisticallysignificant result at p value of 0.05 between all groups. On evaluating the co level in smoking group 53.3%presented with higher CO level and 60% chewers presented with lower CO level. In control group 100%were under no risk.Conclusion: The salivary flow rate is reduced in tobacco users in either form. Since smoking group is athigher risk monitoring of carbon monoxide level can be used as the important tool in motivating the tobaccousers to quit the habit.Aim: To assess salivary flow rate and carbon monoxide level among smokers, tobacco chewers and controlgroup.